Harnessing the reactivity of ortho-formyl-arylketones: base-promoted regiospecific synthesis of functionalized isoquinolines. Issue 57 (27th June 2019) - Mishra, Pawan K.; Verma, Shalini; Kumar, Manoj; Kumar, Ankit; Verma, Akhilesh K.
Abstract : An efficient and base-mediated one-pot regiospecific synthesis of structurally diversified isoquinolines and benzo[ h ] isoquinolines from easily accessible ortho -formyl-arylketones and aryl/(het)arylmethanamines has been described. Abstract : An efficient and base-mediated one-pot regiospecific synthesis of structurally diversified isoquinolines and benzo[ h ] isoquinolines from easily accessible ortho -formyl-arylketones and aryl/(het)arylmethanamines has been described. Challenging 3-alkynyl/alkenyl isoquinolines and bis-isoquinolines were easily attained through this developed chemistry, which can be further used for various organic transformations. Operational simplicity, high atom-economy, broad substrate scope, functional group tolerance and applicability towards large scale synthesis are the advantageous features of this developed methodology.